Ayurvedic Management of Facial Paralysis - A Single Case Study - Rathore, Monika; Sharma, Gyan Prakash; Sharma, Mahesh Kumar; Sharma, Renu (International Research Journal of Ayurveda & Yoga, 2022)
Bell’s palsy or acute idiopathic lower motor neuron facial palsy are similar to Ardita vata presenting with palsy on one side of the face. Sudden paralysis or weakness of the muscles on one side of the face controlled by the facial nerve characteristics this condition. Bell’s palsy is an idiopathic, immune-mediated condition that is thought to be triggered by an infection. In today’s science, steroid medication is the preferred treatment for full facial palsy. A 66-year-old person was diagnosed with Ardita vata as a result of a nor bearing pain in left ear and was treated with Mahamasha taila Nasya and oral Ayurvedic medicines, as well as two Panchakarma sessions. The treatment lasted four months in total, but significant benefits were shown after just one month, indicating practically complete recovery without the use of any additional drugs. The patient had the identical ailment in the right side of his face 5 years ago, and he received complete relief after 2 years of allopathic treatment. This instance serves as proof of the efficacy of Ayurvedic treatment in the treatment of Ardita vata (Bell’s palsy) and as a proposal for more research on a larger number of patients.